Pengaruh Persepsi Harga, Persepsi Kualitas dan Promosi Terhadap Keputusan Pembelian Kawasaki Ninja 250 - Mochamad Reza; Imroatul Khasanah (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
The problem that occurs is a decrease in market share over the past four years and a decline in sales of Kawasaki Ninja 250 motorcycles indicates a decrease in the results of the decision to purchase a Kawasaki Ninja 250 motorcycle. The purpose of this study is to analyze the effect of price perceptions, quality perceptions and promotions on Kawasaki Ninja purchasing decisions 250. The population selected in this study were all Diponegoro University students. The number of samples used in this study were 73 Diponegoro University students who were still active and had purchased Kawasaki Ninja 250 motorcycles. The sampling technique in this study was the purposive sampling method. Data collection method is to use a questionnaire. The data analysis method used is multiple linear regression. Based on research, price perceptions, quality perceptions and promotions have a positive effect on purchasing decisions of the Kawasaki Ninja 250. Variations in employee performance can be explained by independent variables namely price perception, quality perception and promotion by 62.7%